MENGURAI MAKNA DI BALIK HURUF: PENGALAMAN GURU KELAS INKLUSI MENGIDENTIFIKASI DAN MENANGANI MURID DENGAN DISLEKSIA DI SDN 2 NGLANGITAN - DWI PUJI RATNAWATI; LIFTIAH; ALI FORMEN (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article describes the real experience of a classroom teacher at SDN 2 Nglangitan, Tunjungan, Blora, in identifying and managing a student with the pseudonym AS who showed symptoms of dyslexia. The main problem faced is the lack of teacher training and special assistance teachers in inclusive elementary schools, especially in rural areas. The purpose of this article is to explore the process of early identification of dyslexia, intervention strategies implemented, obstacles encountered, and positive impacts achieved. The method used is a qualitative case study approach based on direct observation, in-depth interviews with classroom teachers, and analysis of AS's learning documents over a period of two months. The results showed that AS experienced classic symptoms of dyslexia including difficulties distinguishing symmetrical letters (b-d, p-q), reversed reading, very slow reading speed, and a gap between good oral abilities and poor written abilities. The classroom teacher played a strategic role in early identification through systematic observation, simple assessment instruments, and collaboration with parents. Intervention strategies included multisensory methods, differentiated instruction, modification of teaching materials (enlarged spacing, colored paper, font adjustment), additional time, and positive reinforcement. The main obstacles were the lack of special training, limited facilities, large class sizes, and the absence of special assistant teachers. Despite these limitations, the intervention had a positive impact: AS's reading ability began to improve, letter reversal errors decreased, self-confidence increased, and participation in non-reading class activities improved. This experience confirms that classroom teachers can be the frontline in early detection and management of dyslexia even with limited resources, but systematic support from the government is still urgently needed.